Building an evaluation infrastructure to capture process and progress within a Clinical and Translational Science Awards hub - Padek, Maggie; Mudaranthakam, Dinesh Pal; Pepper, Sam; Penne Mays, Mary; Ellis, Shellie D. (Journal of clinical and translational science, 2025)
To improve its management capacity, Frontiers Clinical and Translational Science Institute overhauled its evaluation infrastructure to be comprehensive, efficient, and transparent in demonstrating outputs and outcomes. We built a platform that standardized measures across program areas, integrated continuous improvement processes, and reduced the data entry burden for investigators. Using the Utilization-Focused Evaluation Framework, we created logic models to identify appropriate metrics. We built the evaluation data platform within REDCap to capture requests, events, attendance, and outcomes and to push work processes to Navigators. We initiated a membership model to serve as the backbone of the platform which allowed tailored communication, demographic data capture, and reduced data entry burden. The platform consists of nine REDCap projects across multiple programmatic areas. Using REDCap Dynamic SQL query fields and External Modules, the membership module was integrated into all forms to check and collect membership before service access. Data is synched to a dashboard for tracking outputs and outcomes in real-time. Since the launch of the evaluation platform in Fall 2022, Frontiers has increased its workflow efficiency and streamlined continuous improvement communication. The platform can serve as a model for other hubs to build efficient processes to create comprehensive and transparent evaluation plans.